2017
DOI: 10.4103/0970-9185.214312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyvinyl chloride, curved reinforced, and straight reinforced endotracheal tubes for tracheal intubation through Airtraq™ laryngoscope in anesthetized patients

Abstract: Background and Aims:The Airtraq™ video laryngoscope facilitates tracheal intubations in patients with difficult airway or cervical spine immobilization. However, curved reinforced tracheal tube and straight reinforced tracheal tubes are useful where neck of the patient is likely to be moved or flexed or if patient is in prone position, wherein nonreinforced endotracheal tube (ETT) might get kinked and/or compressed. We compared intubation success rate of curved and straight reinforced tracheal tubes with polyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Kush Goyal et al . [ 5 ] also considered the same while using Airtraq. In a study done by Dimitriou et al .,[ 12 ] the time elapsed from inserting the blade between the teeth to the endotracheal tube crossing the vocal cords as evidenced by visual confirmation by the anaesthesiologist was considered as the duration of intubation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kush Goyal et al . [ 5 ] also considered the same while using Airtraq. In a study done by Dimitriou et al .,[ 12 ] the time elapsed from inserting the blade between the teeth to the endotracheal tube crossing the vocal cords as evidenced by visual confirmation by the anaesthesiologist was considered as the duration of intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The intubation success rate for different types of endotracheal tubes emerging from the Airtraq laryngoscope in anaesthetised patients was 100% for PVC tracheal tubes and 78.5% for SRT in a previously published study and it was 92.5% and 85% while comparing CRT and SRT in another study. [ 5 12 ] Similarly, Toshiyuki Minonishi et al . [ 6 ] described a higher number of insertion attempts with the use of SRT than with CRT (2.4 ± 1.4 vs. 1.2 ± 0.5) through Airway scope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PVC tube was selected over the flexometallic tube as it has been shown that the success rate of intubation is better with PVC tube under videolaryngoscopic view with similar rates of airway trauma. 1 Although both rigid and flexible fiberoptic scope could be used in this situation under videolaryngoscope guidance, we felt that using a rigid bronchoscope would provide us better control over the instrument.…”
mentioning
confidence: 99%